Relationship Between Sleep Quality and Quality of Life in Diabetic Ulcer Patients - Fikar Lanjari, Zul; Prihatiningsih, Dwi; Susanti, Indah (Java Nursing Journal, 2023)
Background: Diabetes mellitus (DM) is a significant prevalence that occurs making Indonesia ranked sixth in the world. Diabetes mellitus can totally affect the quality of life of diabetic patients with complications, ulcers are complications that affect the quality of life of DM patients. One of the factors that can affect the quality of life of DM patients is sleep quality. Purpose: Knowing the relationship between sleep quality and quality of life in patients with diabetic ulcers. Methods: This type of research is analytic research with a correlational design with a cross-sectional approach. The sampling technique in this study was total sampling with a sample size of 36 respondents. Data analysis using the Chi-square test. Results: It was found that there were 32 respondents (88.9%) experiencing moderate sleep quality and there were 30 respondents (83.3%) who had a negative quality of life. Results: statistical test of the relationship between sleep quality and quality of life showed a statistical test p value = 0.662 or a significance value> a = 0.05, which means that there is no significant relationship between sleep quality and the quality of life of patients with diabetic ulcers. Conclusion: There is no relationship between sleep quality and the quality of life of patients with diabetic ulcers at the Griya puspa wound care clinic, Sleman Regency. Researchers suggest that respondents who have poor sleep quality are expected to improve their quality of life by improving physical health, leisure time, independence, managing emotions and performing good ulcer care.